2012
DOI: 10.1063/1.3672189
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and cost-effective fabrication of selectively permeable calcium-alginate microfluidic device using “modified” embedded template method

Abstract: In this paper, we have presented a non-lithographic embedded template method for rapid and cost-effective fabrication of a selectively permeable calcium-alginate (Ca-alginate) based microfluidic device with long serpentine delay channel. To demonstrate the versatility of the presented method, we have demonstrated two different strategies to fabricate serpentine long delay channels without using any sophisticated microfabrication techniques, in formal lab atmosphere. The procedure presented here, also, enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…For the external gelation fabrication method, the molecular weight cutoff (MWCO) of the membrane has been placed between 60 and 70 kDa (≈3–6 nm) by multiple sources [7,12,20,25,37,47]. It is essential to distinguish pure diffusion from surface erosion, the latter being a combination of hydrodynamic drag and membrane swelling [13,48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the external gelation fabrication method, the molecular weight cutoff (MWCO) of the membrane has been placed between 60 and 70 kDa (≈3–6 nm) by multiple sources [7,12,20,25,37,47]. It is essential to distinguish pure diffusion from surface erosion, the latter being a combination of hydrodynamic drag and membrane swelling [13,48].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the versatility of applications, diffusivity quantification across alginate bio-membranes of various geometric shapes and sizes differing by nature and extent of cross-linking and coatings has been extensively researched [6,7,8,9,10,11,12,13]. In conjunction, indirect diffusivity estimations using pore size characterization by various scanning probe microscopy (SPM) methods have been documented [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Even after membrane burst, the average release from alginate films ( M AGCa  = 81%) is approximately twice that calculated from chitosan films ( M CD  = 42%) from which, it could be inferred that alginate films are more porous than chitosan films and hence, the justification of using chitosan for slowing down the release rate of compounds from alginate membranes (Gaserod et al 1999; Asthana et al 2012). Theoretically, an increase in CaCl 2 for the alginate films in conjunction with an increase in PG content for the chitosan films, should increase the porosity of the films, and hence the diffusion rate (Madsen et al 2011; Simpliciano & Asi 2012); however, no discernible trends were observed as a result of varying the aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 laser was applied to induce glass strip peeling off to form microchannels on soda lime glass substrates, as reported by Wang and Zheng. 20 Asthana et al 21 presented a nonlithographic embedded template method for rapid and cost-effective fabrication of a selectively permeable calcium-alginate (Ca-alginate) based microfluidic device with long serpentine delay channel. Finally, surface modification of cyclic olefin copolymer (COC) by 2-methacryloyloxyethyl phosphorylcholine monomer using photografting technique was reported by Jena and Yue, 22 showing the resistance to both protein adsorption and cell adhesion in COC-based microfluidic devices.…”
mentioning
confidence: 99%
“…It was a successful conference providing a highly interactive forum that brought together approximately 200 researchers of different disciplines from more than 20 different countries and regions. This special issue is dedicated to the original contributions that were presented at the conference and covers a wide range of research directions from both fundamental and practical application of microfluidics and nanofluidics, including acoustofluidics, 1,2 biosensor 3 and diagnosis, 4 dielectrophorsis, 5-7 droplet microfluidics, [8][9][10][11][12][13][14][15] electrokinetic flow 16,17 and electrophoresis, 18 micro-and nanofabrications, [19][20][21] as well as surface modification. 22 Beginning with acoustofluidics, Wang, Jalikop, and Hilgenfeldt 1 reported a bubble microfluidic device to filter, enrich, and preconcentrate particles of selected sizes through oscillating microbubbles of radius 20-100 lm driven by ultrasound.…”
mentioning
confidence: 99%